Special (vestibular) training of servicemen - Afonin V.M (Kharkov National Pedagogical University, 2011)
It has been shown that conditions of professional activity of airmobile servicemen require from them, in addition to excellent proficiency in military armament and materiel, high level of physical qualities and movement coordination development. It is essential to have high practice of vestibular apparatus, which helps to resist such negative feature as air sickness. The essences of term air sickness, its negative consequences for professional activity are highlighted. Possible tendencies of work in terms of enhancing organism resistance to air sickness (according to the analysis of publications and practical experience) are investigated.